Hydrobiology of the Great Man-Made river reservoirs - Bieyw, Salih Hamd; Muhamad, Aabdallah Iibrahim; Qadih, Maseud Muhamad; Aleayib, Muhamad Aldarawi; Altuwmi, Fatimat; Alsaahili, Nasir Muhamad (Al-Mukhtar Journal of Sciences, 1997)
The Man-Made reservoirs are considered as newly established aquatic ecosystems in different areas. Hence it is vitally important to conserve the quality of their waters intended for human, industrial, and Agricultural purposes and the conveying pipe system. The present ecological studies were conducted during June 1992 to June 1993 in order to evaluate the presence of Micro-organisms, algae, aquatic plants and animals, beside the chemical changes of the water. The results revealed that there were observed changes between the waters of sarir well-fields ans that of the reservoirs as it expose to the natural ecological factors. The results have also shown diverse Micro-organisms including sulfur reducing bacteria, 11 species of algae, 3 species of aquatic plants, and 11 families of aquatic insects. Twelve families of visitor insects were also observed or collected in the vicinity of the reservoirs. Aquatic vertebrates were absent from all reservoirs, except a single species of frog that was reported from Omar Al-mukhtar reservoir at sloug. In conclusion, the biotypes reported from the different man-made reservoirs (Sloug, Ajdabia and Sirt) are still considered natural components of any open aquatic ecosystem devoting of any harmful organism.